Efektivitas Penerapan Program Adiwiyata dalam Membentuk Perilaku Peduli Lingkungan (Studi Kasus di SDN 008 Tana Tidung) - Khresma Tombang; Maman Rumanta; Sandra Sukmaning Adji (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the effectiveness of the Adiwiyata Program implementation in shaping environmentally conscious behavior at SD Negeri 008 Tana Tidung using the CIPP (Context, Input, Process, Product) evaluation model. The research method used is a qualitative descriptive approach with an evaluative research type. Data were collected through observation, interviews, questionnaires, and documentation involving the principal, the Adiwiyata team, teachers, staff, and students. Data analysis was conducted using the CIPP evaluation model to assess the suitability of the context, the availability of input, the implementation of the process, and the results of the program. The results show that the Adiwiyata Program has been running quite effectively. In terms of context, the program is aligned with the school's vision and the established culture of environmental care, although the integration of the environmental curriculum is not yet comprehensive. In terms of input, the school has adequate facilities and infrastructure, but its management is not yet optimal. In terms of process, various environmental activities have been carried out routinely and participatory, but the implementation is not consistent and community involvement is still limited. In terms of product, the program is able to increase students' awareness and behavior of environmental care, although the behavioral changes are not yet evenly distributed and sustainable. The conclusion of this study indicates that the Adiwiyata Program at SD Negeri 008 Tana Tidung is quite effective in fostering environmentally conscious behavior. However, further strengthening of curriculum integration, infrastructure management, consistent program implementation, and partnerships with various parties is needed to optimally enhance the program's sustainability and effectiveness.   Keywords: Adiwiyata, Program Effectiveness, Environmental Care, Environmental Behavior